A facile "bottom-up" approach to prepare free-standing nano-films based on manganese coordination clusters. - SCHMITT, WOLFGANG (My University, 2013)
We present herein a novel method to prepare free-standing Dried Foam Films (DFFs) whereby individual polynuclear manganese complexes cover quantitatively the holes of micro-grids; the fabricated, homogeneous films have a cross-sectional thickness of only ca. 5 nm and are characterised by high mechanical stability
PUBLISHED
Keywords: Chemistry